La "Dactylo Grammatica" de Juan Caramuel: entre el lenguaje de signos y las lenguas universales - Martínez Gavilán, María Dolores (Boletín de la Sociedad Española de Historiografía Lingüística, 2018)
One of the great contributions to linguistic knowledge in the 17th century is the beginning of the movement for the creation of artificial languages, with the purpose of attaining efficient tools for universal communication, independent from individual languages. Most projects from that century were graphic systems, although a few attempts to build sign languages (based upon hand and finger movements) can also be found. One of the earliest schemes is Dactylo Grammatica, devised by Juan Caramuel (1606-1682). By providing a detailed description of this work, this study aims at bringing it to light and defend its inclusion in sign language studies.